PERAN MENANAMKAN NILAI KEWIRAUSAHAAN PADA ANAK USIA DINI DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Masitha Fahmi Wardhani; Diana Puspitasari; Miftachul Mujib (BISECER (Business Economic Entrepreneurship), 2022)
AbstractIn the era of the industrial revolution 4.0, digital technology plays a role in all aspects of human life, where this condition requires everyone to prepare themselves to be able to compete in the midst of many human resources being replaced by robots or machines. One of the early self-preparations is to instill entrepreneurial character values, namely creativity, hard work, independence, leadership, risk taking, and orientation to action in early childhood which is also a step in realizing the vision of the RA Terpadu Al-Qolam School Semarang. The research method used is qualitative with a case study approach. This study aims to reveal the actual conditions of inculcating entrepreneurial values with children being taught to be creative in making products, understanding product prices, and marketing them at RA Terpadu Al-Qolam Semarang. The results of these activities can be used as a way to instill entrepreneurial character values from an early age with the hope that in the future they will form a superior generation and even be able to create jobs.Keywords: entrepreneurial value, early childhood, industry 4.0